DISCOVERY LEARNING MODEL IN TEACHING WRITING DESCRIPTIVE TEXT FOR SEVENTH GRADE OF SMP SWASTA SRO MATITI - Puan Suri Mira Annisa,; Reny Simanullang, (Journal of Innovation Research and Knowledge, 2022)
This study was about Discovery Learning Model in Teaching Writing Descriptive Text for Seventh Grade of SMP SWASTA SRO MATITI. The type of research method in this study is descriptive qualitative research. The data collection used in this study is observation, interview, questionnaire and documentation. The results of this study indicate that the teacher has implemented the discovery learning model well. Student responses to the discovery learning model are different, this is because the intellectual knowledge of each student in expressing ideas in written form in English is different. Some of the challenges faced by teacher after applying the discovery learning model in learning teaching write descriptive texts, there are the simulation stage, the problem statement stage and the data processing stage. This was revealed when the researcher observed students and interviewed teacher after the teaching and learning process was completed.